Diagnosis of distal radial injuries in children - Shevchenko, Stanislav; Korolkov, Oleksandr; Mаrtiuk, Victor; Yakovenko, Inna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The article deals with the problem of early diagnosis of traumatic epiphysiolysis in the distal radius “without displacement of epiphysis” (type I by the Solter-Harris classification, 1963). Clinical, radiological and sonographic examinations were conducted in 58 cases with an injury of the distal forearm. A method of early diagnosis of distal epiphysiolysis of the radial bone and a technique of ultrasonographic examination were developed; sonographic semiotics of traumatic epiphysiolysises of the distal radial bone “without displacement of epiphysis” is described. An algorithm for diagnosing injuries in the distal part of the radial bone was developed.